2017
DOI: 10.1103/physreva.95.063829
|View full text |Cite
|
Sign up to set email alerts
|

Quantum metrology of spatial deformation using arrays of classical and quantum light emitters

Abstract: We introduce spatial deformations to an array of light sources and study how the estimation precision of the interspacing distance d changes with the sources of light used. The quantum Fisher information (QFI) is used as the figure of merit in this work to quantify the amount of information we have on the estimation parameter. We derive the generator of translationsĜ in d due to an arbitrary homogeneous deformation applied to the array. We show how the variance of the generator can be used to easily consider h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 61 publications
3
32
0
Order By: Relevance
“…𝑔 𝑗 𝑘 𝑑𝜃 𝑗 𝑑𝜃 𝑘 (10) and computing 𝑑𝑈 = −𝑖𝑈 𝑗 𝐻 𝑗 𝑑𝜃 𝑗 , we find that the metric explicitly depends on the generators from Eq. ( 7) through…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…𝑔 𝑗 𝑘 𝑑𝜃 𝑗 𝑑𝜃 𝑘 (10) and computing 𝑑𝑈 = −𝑖𝑈 𝑗 𝐻 𝑗 𝑑𝜃 𝑗 , we find that the metric explicitly depends on the generators from Eq. ( 7) through…”
mentioning
confidence: 98%
“…However, much less is known about the corresponding bounds for the simultaneous estimation of multiple parameters. Multiparameter quantum metrology finds many important applications in fields as diverse as imaging [4][5][6], field sensing [7][8][9], sensor networks [10][11][12], and remote sensing [13] to cite but a few examples. In this case, the QCRB is a matrix inequality and the ultimate bound is generally not saturable for all parameters.…”
mentioning
confidence: 99%
“…Research on quantum antennae has important applied signifi cance. These systems can act as sources in new areas such as quantum microscopy [6,7], quantum sensing [8], quantum communication [9], and quantum optical computers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tsang et al showed that the far field quantum state of light retains a significant amount of information about the separation of two identical incoherent point sources, even when their angular separation approaches zero [12]. Moreover, this information can be extracted with a suitable measurement [13], for example using spatial-mode demultiplexing [14]. Recently, a series of experiments demonstrated sub-Rayleigh resolution for two incoherent point sources, using image inversion interferometry [15,16], digital holography [17], and TEM 01 heterodyne detection [18].…”
mentioning
confidence: 99%